2014
DOI: 10.3390/ijerph111212562
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Program Outcomes to Encourage Policymaker Support for Evidence-Based State Tobacco Control

Abstract: Tobacco use, the leading cause of preventable death in the U.S., can be reduced through state-level tobacco prevention and cessation programs. In the absence of research about how to communicate the need for these programs to policymakers, this qualitative study aimed to understand the motivations and priorities of policymakers in North Carolina, a state that enacted a strong tobacco control program from 2003–2011, but drastically reduced funding in recent years. Six former legislators (three Democrats, three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Research should examine the processes that impede the adoption of comprehensive public smoke-free policies and voluntary adoption of such policies in personal settings in Georgia. Relatedly, determining ways in which community engagement and coalition building can be fostered are critical in advancing smokefree policy legislation (Schmidt et al 2014). For public health practitioners, our findings suggest that Georgians are supportive of public smoke-free policies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Research should examine the processes that impede the adoption of comprehensive public smoke-free policies and voluntary adoption of such policies in personal settings in Georgia. Relatedly, determining ways in which community engagement and coalition building can be fostered are critical in advancing smokefree policy legislation (Schmidt et al 2014). For public health practitioners, our findings suggest that Georgians are supportive of public smoke-free policies.…”
Section: Discussionmentioning
confidence: 81%
“…One might be that constituents are not highly engaged with their lawmakers (Berg et al 2015c), which is critical in advancing tobacco control legislation (Flynn et al 1997). This is particularly important given the importance of lobbying for influencing public policy, whether the influence comes from the public health community or the tobacco industry (Schmidt et al 2014;Berg et al in press). Another explanation may stem from policymakers' misconceptions about the negative health impacts of SHSe or the economic and public health benefits of smoke-free policies (Flynn et al 1998;Thrasher et al 2015;Berg et al in press).…”
Section: Discussionmentioning
confidence: 99%
“…As such, engaging constituents with policymakers is critical. 21 Moreover, concerns were raised about the impact of increased tobacco taxes on state economies and particularly in relation to people crossing state borders to buy cigarettes at lower prices. However, legal border crossing to purchase cigarettes and avoid tobacco taxes has been found to be infrequent and have little economic impact.…”
Section: Discussionmentioning
confidence: 99%
“…21 Alternatively, legislators may have misconceptions regarding the economic impact of tobacco taxes. 22-24 The decreased likelihood of supporting tobacco control legislation in these regions also could reflect the fact that the personal values and attitudes of legislators are major determinants of voting decisions. 25 In one study, Oklahoma legislators reported that personal beliefs accounted for 63% of all voting decisions.…”
Section: Discussionmentioning
confidence: 99%
“…20 Moreover, lobbying, from both the public health side and the tobacco industry, plays a key role. 20,22 …”
Section: Discussionmentioning
confidence: 99%